2014
DOI: 10.1021/jm500777s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Sirtuin 2 (SIRT2) Inhibitors Using a Fragment-Based Approach

Abstract: Sirtuin 2 (SIRT2) is one of the sirtuins, a family of NAD(+)-dependent deacetylases that act on a variety of histone and non-histone substrates. Accumulating biological functions and potential therapeutic applications have drawn interest in the discovery and development of SIRT2 inhibitors. Herein we report our discovery of novel SIRT2 inhibitors using a fragment-based approach. Inspired by the purported close binding proximity of suramin and nicotinamide, we prepared two sets of fragments, namely, the naphthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 62 publications
(60 reference statements)
1
81
0
1
Order By: Relevance
“…Use of three structurally unrelated sirtuin inhibitors, including compound 64, 35 the most potent and specific SIRT2 inhibitor described to date, and cambinol, a previously described putative pan-sirtuin inhibitor, 47,48 largely confirmed our working hypothesis, as incubation of cells in the presence of these compounds Figure 4 Cambinol interferes with the molecular execution of necroptosis. (a) Cambinol (100 μM) or necrostatin-1 (20 μM)-treated L929 cells were incubated in the presence of hTNF (1 ng/ml) for 20 min and the phosphorylated status of JNK determined by western blot (n = 3).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Use of three structurally unrelated sirtuin inhibitors, including compound 64, 35 the most potent and specific SIRT2 inhibitor described to date, and cambinol, a previously described putative pan-sirtuin inhibitor, 47,48 largely confirmed our working hypothesis, as incubation of cells in the presence of these compounds Figure 4 Cambinol interferes with the molecular execution of necroptosis. (a) Cambinol (100 μM) or necrostatin-1 (20 μM)-treated L929 cells were incubated in the presence of hTNF (1 ng/ml) for 20 min and the phosphorylated status of JNK determined by western blot (n = 3).…”
Section: Discussionsupporting
confidence: 65%
“…32 We therefore postulated that one or several members of this family might be involved in the signaling pathway leading to necroptosis, an hypothesis recently suggested by an independent study. 33 Three structurally unrelated sirtuin inhibitors (EX-527, 34 compound 64 35 and cambinol 36 ) protected L929 cells from TNF-induced cell death (Figures 2a-c, see also Supplementary Figure S2 for a typical flow cytometry data plot). Cambinol was selected for further characterization throughout this study and shown to selectively protect L929 cells from TNF-induced necroptosis (Figure 2e) but not FAS-dependent apoptosis (Figure 2d).…”
Section: Intracellular Nadmentioning
confidence: 99%
“…This finding might indicate that TcSir2rp3 is the target of salermide in T. cruzi. Several sirtuin inhibitors have recently been developed, aiming to obtain highly specific inhibitors for each one of the sirtuins (62,63). Therefore, it would be possible to develop more potent inhibitors to T. cruzi sirtuins.…”
Section: Discussionmentioning
confidence: 99%
“…As we will describe later in this article, when using FBDD to target enzymes, it is possible to use enzymatic assays to directly screen for fragment inhibitors at high compound concentration. In fact, it has been reported in many literature literature references that the fragments deconstructed from known higher molecular weight enzyme inhibitors still retain partial inhibition activities as the parent compounds [37,38].…”
Section: Fragment-based Drug Discovery: Concepts and Methodsmentioning
confidence: 99%
“…To target Sirtuin 2 (SIRT2), a NAD + -dependent deacetylase that acts on both histone and non-histone targets, Cui et al [37] synthesized a focused fragment library based on two known inhibitors of the Sirtuin family: suramin and nicotinamide [37]. Their strategy was based on the fact that the binding sites of suramin and nicotinamide are proximal providing the possibility of linking the two fragment anchors together to create high affinity inhibitors [37].…”
Section: Citationmentioning
confidence: 99%